A influência do implante dentário na qualidade de vida: estudo preliminar - Silva Junior, Aderbal Coelho da (2014)
Objective: The aim of this pilot study is the influence of dental implants in patient´s quality of life based on a satisfaction questionnaire answered by patients treated with conventional prostheses and implant supported prostheses. Materials and Methods: A satisfaction questionnaire OHIP 14 (Oral Health Impact Profile), answered by a total of 40 patients who underwent to dental rehabilitation at Universidade do Grande Rio, graduate and postgraduate clinic, shared by four groups: 1- patients treated with conventional prostheses, 2- patients treated with implant supported overdentures, 3- patients treated with fixed implant prostheses (protocols), 4- patients treated with metal-ceramic fixed implant prostheses or single implant crowns. The answers were tabulated, and Kruskal Wallis test was used to perform statistical analyses. Results: No statistical significance was found comparing the four groups. Despite a less satisfactory performance awarded by conventional prostheses and followed by overdentures answers. The significance value was P < 0,05. Conclusion: The influence of oral prosthetic rehabilitations in quality of life seems to be related to patient´s subjective factors, more than a specific kind of prostheses or implant installation. The increase of a sample number and the incorporation of other kinds of analogue evaluation could enhance the understanding on factors related to patient´s satisfaction